HUMAN CAPITAL MANAGEMENT AND COMPANY PERFORMANCE; CASE STUDY OF COFFEE DREGS BRIQUETTES; ALTERNATIVE FUELS - Hartoyo; Muhammad Dhafi Iskandar (MANAJEMEN DEWANTARA, 2024)
The success of an organization is contingent on the commitments and outcomes of human resource management, which is able to transform employee development into an increase in the individual value of human capital (human capital) as an investment in company assets in a competitive labour market. The purpose of this paper is to conduct a literature review to assess the human capital management strategies implemented by PT Energia Kopi Kreasindo in response to the evolution of human resources. When discussing HR governance, strategy, management, and human capital, leadership and human capital income factors should be considered. The study's findings indicate that there are a number of things that can be done to improve the management of employees, which will ultimately increase the productivity of the investment company's "employees"; preparation for the development of skills, knowledge, and competencies; and education to create superior human capital.